Synthesis and structural characterization of Ti(III) and Mo(III) complexes supported by PNP pincer ligands - Ruivo, Rita; Alves, Luis; Martins, Ana (European Journal of Chemistry, 2023)
New Ti(III) and Mo(III) complexes of formulae [(PNP-Ph)TiCl3], 1, and [(PNP-iPr)MoCl3], 2, where PNP-Ph = N,N’-bis(diphenylphosphino)-2,6-diaminopyridine and PNP-iPr = N,N’-bis(diisopropylphosphino)-2,6-diaminopyridine were synthesised, in moderate yields, by reaction of MCl3·(THF)3 (M = Ti and Mo) with the suitable ligand precursor. The solid-state molecular structures of complexes 1 and 2 were obtained by single-crystal X-ray diffraction. Crystal data for C37H41Cl3N3O2P2Ti (1·(C4H8O)2): triclinic, space group P-1 (no. 2), a = 10.0945(4) Å, b = 10.3002(4) Å, c = 18.6233(7) Å, α = 92.412(2)°, β = 91.108(2)°, γ = 101.705(3)°, V = 1893.65(13) Å3, Z = 2, µ(MoKα) = 0.559 mm-1, Dcalc = 1.361 g.cm-3, 20760 reflections measured (2.021 ≤ Θ ≤ 27.130), 8327 unique (Rint = 0.0399, Rsigma = 0.0414) which were used in all calculations. The final R1 was 0.0316 (I > σ(I)) and wR2 was 0.0850 (all data). Crystal data for C17H33Cl3MoN3P2 (2): tetragonal, space group I41/a (no. 88), a = b = 19.468(4) Å, c = 31.711(6) Å, α = β = γ = 90°, V = 12019(5) Å3, Z = 16, µ(MoKα) = 0.816 mm-1, Dcalc = 1.202 g.cm-3, 42367 reflections measured (2.569 ≤ Θ ≤ 25.347), 5498 unique (Rint = 0.1408, Rsigma = 0.1293) which were used in all calculations. The final R1 was 0.1005 (I > σ(I)) and wR2 was 0.3194 (all data). The coordination geometry around the titanium and molybdenum centers is best described as octahedral, with three donor atoms of the PNP ligand and one chlorine atom occupying the equatorial plane. The axial positions of the octahedron are occupied by the other two chlorido ligands in both complexes. The NH spacer groups in the PNP ligands have an important role in the establishment of hydrogen bonds between the complexes and molecules of the solvent or neighbouring species.